If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 20 = 92 Reorder the terms: 20 + 2x = 92 Solving 20 + 2x = 92 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 2x = 92 + -20 Combine like terms: 20 + -20 = 0 0 + 2x = 92 + -20 2x = 92 + -20 Combine like terms: 92 + -20 = 72 2x = 72 Divide each side by '2'. x = 36 Simplifying x = 36
| 13a+9b=13750 | | 9x=10+3x | | 13a+9b=13 | | x+3.1=1.6 | | x+.1=1.6 | | -x+3=-45+5x | | a^2+a=25 | | 7-2x=-4+23 | | y=100+75 | | 2a^2-16ab+14b^2=0 | | 40x+8(1.5)=525 | | (x-(2-5i))(x-(2+5i))=0 | | 4x-2-5x=-7 | | 81+256=625 | | 3-6x=3x-2x-46 | | 0.000579a^2-a+286.25=0 | | 6-5n=n+9 | | p+7=1.1 | | -7/8x-1/2=3/16x+5 | | 1x+2x+3x=82 | | 18+32=50 | | -(7x^3+2x^2-3)+(5x^2-30)= | | -6=2x-5x+3 | | 35x^2+21x= | | 5(6t-3)=6(3t-1) | | 2x+y(0.4+0.1)=5 | | 8b-7(1-19b)=17(b-15) | | 9x(x+2)=0 | | 5x-9-x=2 | | -4+3x+x=-40 | | -8+3x=16+9x | | 2x-3+8x-7=4x+6x+10 |